Mutu Pelayanan, Mutu Produk Franchise Klenger Burger dan Kepuasan Pelanggan di Tomang Jakarta Barat - - Riana; Amiruddin Saleh; Darwin Kadarisman (Institut Pertanian Bogor, 2013)
Franchise business growth at present get tremendous progress. This can be proved by a variety of franchise businesses in the area of food. The global economic crisis that is currently happening more and encourage franchise owners to make this franchise should be able to survive. To preserve what has been achieved and increase competitive advantage with a similar product franchise Burger Klenger know and get feedback from customers about the quality of services and products to customer satisfaction has been given so far. This study used to descriptive survey with primary and secondary data, and analyzed by SPSS to explain the IPA and CSI approach.Suitability analysis Klenger Burger franchise service quality attributes that there are 13 very important factors. The determination to make up the quality of service shown in the diagram Cartesians. Attributes contained in Quadrant C is the low priority of five attributes. This attribute must immediately make improvements. It has also reinforced the value of CSI quality of service, product quality Klenger Burger franchise and customer satisfaction is of 84,3%. The CSI is located between the range of 0,81 to 1 which means that customers feel very satisfied customer satisfaction performance.Quality of service, product quality and satisfaction Klenger Burger franchise get enough value from their customers satisfied, so the franchise Burger Klenger must continually strive to maintain, repair attribute less and keep the level of satisfaction can be increased.